2017
DOI: 10.1109/tvt.2016.2564106
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Analysis of Joint Transmission CoMP With Adaptive Modulation

Abstract: Joint transmission (JT)-based Coordinated Multipoint (CoMP) systems achieve high performance gains by allowing full coordination among multiple cells, transforming unwanted intercell interference into useful signal power. In this paper, we present an analytical model to perform adaptive modulation for a typical JT CoMP system, consisting of three transmission points, under a target bit error rate (BER) constraint. Probability density functions of the signal-to-interference-plus-noise ratio (SINR) are derived f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 12 publications
(12 reference statements)
1
24
0
Order By: Relevance
“…The full interference model means that the interference for n-th UE comes from all SBSs except the n-th SBS. The analytical results of the queue-violation probability are obtained by (9), (15), (16) and (28). As traffic increases, the the queue-violation probability also increases.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The full interference model means that the interference for n-th UE comes from all SBSs except the n-th SBS. The analytical results of the queue-violation probability are obtained by (9), (15), (16) and (28). As traffic increases, the the queue-violation probability also increases.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…There are mainly three types of CoMP techniques: coordinated beamforming (CB), coordinated scheduling (CS), and joint transmission (JT). Among these CoMP techniques, the JT-CoMP technique offers the highest performance gains by fully sharing both data and control information among the coordinated base stations (BSs) [3]. However, implementing JT-CoMP faces several critical challenges in practical 5G small cell networks.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that these three JT-CoMP schemes had pros and cons in different aspects. An analytical model was proposed to perform adaptive modulation for a typical JT-CoMP system consisting of three transmission points [3]. The closed-form expressions for the average spectral efficiency were obtained when adopting continuous-rate adaptive mod-ulation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the explosive growth of mobile data stemming from the increasingly prevalence of smart handset devices, the scarcity of spectrum is becoming the bottleneck to boost more capacity of wireless communication [1]. To improve the system capacity, a common trend has emerged with deploying additional low power nodes (LPNs, such as smallcells, femtocells), and improving the spectral utilization, such as Coordinated Multipoint (CoMP) [2]. To fundamentally break through this predicament, an emerging technology using the unlicensed spectrum, called licensed-assisted access (LAA), has been launched into the standardization by Third Generation Partnership Project (3GPP) [3].…”
Section: Introductionmentioning
confidence: 99%